Pengembangan Aplikasi Augmented Reality Untuk Memadukan Baju Kampanye (Studi Kasus: Calon Anggota DPRD Kabupaten Nganjuk) - Ananda Widya Pratama; Herman Tolle; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Party dress is one of the identities of the party in every election, there is a group of people who wear uniform party dresses. Party clothes are used during campaigns to convey party messages and information to the public. The 2019 general election is a general election whose polling is the most complex and stunning of the world. It is this election system that raises challenges for the community because of simultaneous elections. The simultaneous election to elect the president and legislature is evident from the survey results of the Indonesian Survey Circle (2019) showing that "Many legislative candidates (candidates) in their constituencies (electoral districts) have chosen the average election for each legislative candidate. As many as 70.6 percent of the 1,200 did not know the legislative candidates, 25.8 percent already knew the legislative candidates in their electoral districts. In general, only 25.8 percent already know the legislative candidates to be elected in their respective electoral districts. "The survey shows that elections are needed so that people understand the legislative candidates by adjusting to the current era in which technological developments continue to develop. messages and information today are using assistive technology, augmented reality technology is a solution to help resolve the problem, 3D concepts in augmented reality technology can be applied in group selection campaigns by making campaign clothes, a single marker of the author expects the help process of candidates for DPRD members Nganjuk Regency from the general election and giving new innovations in the general election Based on the optimal examination results the marker produced the results correctly FALSE indicates that the marker was not determined or the marker was selected but did not display the infallibility, ie the optimal marker with a size of 15x1 5cm between 30-240cm, markers of 15x20cm between 30-270cm, markers of 20x20cm between 30-300cm, markers of 20x25cm between 30-330cm, and markers of 20x30cm between 30-360cm. Based on the usability testing using the System Usability Scale method, the usability test shows satisfactory results. Based on the questions raised to 10 respondents with a weighting rating scale of 1 (Strongly Disagree) to 5 (Strongly Agree) a usability test result of 81.25 was obtained with a Very Good ranking qualification